2021
DOI: 10.1111/maec.12691
|View full text |Cite
|
Sign up to set email alerts
|

Consistent genetic divergence observed among pelagic Sargassum morphotypes in the western North Atlantic

Abstract: Sargassum natans and Sargassum fluitans are uniquely holopelagic macroalgae, providing open ocean nursery and foraging habitat for commercially and ecologically important species. Recent basin‐wide changes in pelagic Sargassum diversity and distribution have manifested in proliferation of a previously rare morphotype, Sargassum natans VIII, to rival biomass levels of historically dominant S. natans I and S. fluitans III. Precise genetic identification of these morphotypes can improve accuracy and interpretatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…Carbon, nitrogen, and phosphorus content did not differ across morphotypes or spatially but showed temporal variations at Dania Beach (Figure 4). Despite distinct morphological, physiological, and genetic differences across sargasso morphotypes [39,53,54], the lack of differences in nutrient content across morphotypes in our study is similar to the lack of distinctions found between S. fluitans and S. natans (without morphotype distinction) in studies conducted by Lapointe et al (2021) [21] and McGillicuddy et al (2023) [26]. However, Changeux et al (2023) [55] reported local variations of %N across morphotypes sampled in the Mexican Caribbean region.…”
Section: Discussionsupporting
confidence: 77%
“…Carbon, nitrogen, and phosphorus content did not differ across morphotypes or spatially but showed temporal variations at Dania Beach (Figure 4). Despite distinct morphological, physiological, and genetic differences across sargasso morphotypes [39,53,54], the lack of differences in nutrient content across morphotypes in our study is similar to the lack of distinctions found between S. fluitans and S. natans (without morphotype distinction) in studies conducted by Lapointe et al (2021) [21] and McGillicuddy et al (2023) [26]. However, Changeux et al (2023) [55] reported local variations of %N across morphotypes sampled in the Mexican Caribbean region.…”
Section: Discussionsupporting
confidence: 77%
“…Holopelagic Sargassum , a brown macroalgae, drifts at the water’s surface creating a unique and ecologically-significant floating marine ecosystem in the oligotrophic open ocean ( Haney, 1986 ; Wells & Rooker, 2004 ). Presently, two species and multiple morphological forms of holopelagic Sargassum are recognized and distributed throughout the equatorial and western North Atlantic Ocean ( Parr, 1939 ; Butler et al, 1983 ; Goodwin, Siuda & Schell, 2020 ; Dibner et al, 2021 ). At the <1 to 100s of meters spatial scale, holopelagic Sargassum aggregation patterns underpin its ecological value, the dynamic availability of highly localized prey biomass within and beneath the algae, and remote sensing detection and prediction capabilities ( Moser & Lee, 2012 ; Wang & Hu, 2017 ; Wang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other invasive species than Sargassum could have been considered. However, in situ sampling carried out across the Atlantic Ocean in previous studies did not reveal evidence of the occurrence of any other invasive species competitive with Sargassum [11,[20][21][22]. Thus, although it might theoretically be possible, it should not be the case here.…”
Section: Site Number K (Dimensionless)mentioning
confidence: 69%